Iron Deficiency Anemia among School Going Children of Rural Area of Mardan Khyber Pakhtunkhwa - Ullah, Shakir; Amin, Amjad Ali; Khan Rahman, Muhammad Iqbal; Islam, Umair; Muhammad, Noor; Khan, Hamza; Ilyas, Muhammad; Saeed, Usman; Nawab, Abbas; Khalid, Shah (Food, Agriculture and Natural Resources - NETWORKS, 2023)
Iron is essential for normal human growth, including oxygen transport, adenosine triphosphate (ATP) production, DNA synthesis, mitochondrial function, and protection of cells from oxidative damage. Iron deficiency anemia is the most prevalent hematologic disorder in school-going children. Therefore the aims were the study to assess the prevalence of anemia among school-going children of rural areas of Mardan Khyber Pakhtunkhwa. A total of 300 samples were taken from those children of signs and symptoms of Iron deficiency Anemia cross-section survey. Thorough physical Examination, Lab investigations, and Clinical examination. The current research work shows that 1 of 3rd of the school-going children who had signs and symptoms of iron deficiency anemia were affected with iron deficiency Anemia at the ages of 4 to 7 years 40(40%), 7 to 10 years 35(35%) and 10 to 13 years 25(25%) respectively. severe anemia was rare at 10%, moderate anemia at 25% led by the mild type of anemia with a high percentage of 65% on the basis of Hb level. lower class families were more affected by iron deficiency anemia with 60%, children of middle class were less affected by anemia with 35% while children of upper class families were much less affected by anemia which may be due to the socioeconomic state of the family. Therefore it is recommended that iron supplementation and health and nutrition education programs should be strengthened.